Flamingos, salt lakes and volcanoes: hunting for evidence of past climate change on the high Altiplano of Bolivia. (May 2017) - Clark, Nicola; Wallis, Simon
Abstract : Hidden within the vast Bolivian Altiplano are archives of past climate change in the form of remarkable carbonate rocks surrounding lakes long since disappeared. Beyond the Salar de Uyuni, the largest salt flat in the world, lies a relatively untouched realm of volcanoes and salt lakes. Ancient shorelines from intervals in the Altiplano history, when large lakes were more abundant, may hold important information about a time when the climate in this region was punctuated by much wetter phases before present day aridity took a hold. Previous studies in this region have reconstructed robust chronological timelines for such events and highlight two large lake phases over the last 18 thousand years (the Tauca and Coipasa lake phases); however higher resolution climate data are scarce. Current studies on climate proxies from smaller lakes in southern Bolivia may shed light on some of these higher resolution climate events including El Niño–Southern Oscillation (ENSO) events. Laminated tufa found around the palaeoshorelines of the West Lípez Lakes is one such proxy, and can be analysed to investigate the potential roles of annual versus shorter‐term climatic variation in the evolving Altiplano climate at the time.